[INVITED] Magnetic field vector sensor by a nonadiabatic tapered Hi-Bi fiber and ferrofluid nanoparticles. (June 2018) - Layeghi, Azam; Latifi, Hamid
Highlights: A two dimension magnetic fiber sensor based on MF and tapered Hi-Bi fiber in FLM is proposed. A Jones matrix method is used to model the sensor structure. The experimental results are in good agreement with theoretical analysis. The effect of birefringence of MF under applied EMF manifests. Abstract: A magnetic field vector sensor based on super-paramagnetic fluid and tapered Hi-Bi fiber (THB) in fiber loop mirror (FLM) is proposed. A two-dimensional detection of external magnetic field (EMF) is experimentally demonstrated and theoretically simulated by Jones matrix to analyze the physical operation in detail. A birefringence is obtained due to magnetic fluid (MF) in applied EMF. By surrounding the THB with MF, a tunable birefringence of MF affect the transmission of the sensor. Slow and fast axes of this obtained birefringence are determined by the direction of applied EMF. In this way, the transmission response of the sensor is depended on the angle between the EMF orientation and the main axes of polarization maintaining fiber (PMF) in FLM. The wavelength shift and intensity shift versus EMF orientation show a sinusoidal behavior, while the applied EMF is constant. Also, the changes in the intensity of EMF in a certain direction results in wavelength shift in the sensor spectrum. The maximum wavelength sensitivity of 214 pm/mT is observed.